Nutrition Consomption, Dry Matter and Dry Weight Digestability of Bali Cattle Ration in Evacuation Zone At Nongan Vilage, Karangasem - I K. B, Dwipayana; Suryani, N. N.; I G., Mahardika (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
Eruption of Mount agung, happened in August until December 2017 caused many cattle were evacuated. This causes difficulty to get good quality feedder. This research aims to know the nutrient consumption, dry matter and organic matter digestibility of bali cattle rations in area shelter livestock due to the eruption of Mount Agung. Research carried out two stages, i.e. the first phase of field survey to find out the type of the given feed and the second phase was conducted in the laboratory to find out the digestibility of dry matter and organic matter of feed. Results of the research showed, the quality of rations in the livestock shelter area better than ever. Consumption of rations, the digestibility of dry matter and digestibility of organic matter during at the area shelter are higher than before. Kata kunci:   Nutrient intake, dry matter and organic matter digestibility, Bali  cattle